The impact of participation in support groups on mental health of parents having children with autism. (13th November 2019) - Alibekova, R; Kadyrzhanuly, K; Chan, C K; An, S; Gusmanov, A; Yerubayev, Z; Yessimkulova, F; Bekisheva, A; Ospanova, Z; Rakhimova, M
Abstract: Introduction: Whilst there is accumulated evidence about the high prevalence of stress and mood disorders in parents of children with autism, few studies have shown that participating in parental support groups was associated with less mental health problems. This study was aimed to explore the association of participation in support groups with stress and mood disorders in parents of children with autism in Kazakhstan. Methods: Participants (n = 146) were recruited to this cross-sectional survey from autism non-governmental organizations and Republican Children's Rehabilitation Center in Nur-Sultan city during April-December 2018. A 59 item survey consisted of questions on parental socio-demographics, needs, participation in support groups, depression, anxiety and stress (DASS), and Multidimensional Scale of Perceived Social Support (MSPSS). Descriptive, bivariate and multivariate logistic regression analyses were performed in STATA 15. Results: 44.4% of parents reported experiencing stress, and almost half of the sample had elevated depressive (53.7%) and anxiety symptoms (47.4%). 45.3% of participants were members of parental organizations; there were no significant differences in the prevalence of stress and mood disorders among members and non-members of parental support groups. Results of the multivariate logistic regression showed that parents with older autistic children (OR 1.37, p-value 0.001), less family support (OR 0.894, p-value 0.044) and higher income (OR 3.01, p-value 0.025) were more likely to be members of support groups. Conclusions: These findings indicate the need to increase support groups to under-served populations of Kazakhstan's families with autistic children. Additional efforts are needed to strengthen the role of support groups in meeting the emotional needs of the parents. Key messages: Parents of children with autism spectrum disorder experience elevated level of stress and mood disorders; however participation in support groups was not beneficial for relieving parental distress. Further research is warranted to explore the benefits of participation in support groups, and interventions are needed to strengthen the role of support groups in meeting the needs of parents.